1989
DOI: 10.1016/0266-7681(89)90022-3
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Bodies in Tendons

Abstract: At the National Institute of Traumatology in Budapest, a search has been made for foreign bodies in tendons over the last 15 years. 53 foreign bodies have been found in 931 tendons removed at operation and 45 foreign bodies in 950 tendon samples at autopsy. The foreign material was found to be organic in 29 cases, metal in 20 cases and plastic in six cases. In the others, glass, sand, mineral grease and textiles could be detected. In 33 cases the material could not be identified. The foreign bodies were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The use of PLGA and PCL has been problematic, with in vitro data showing poor tendon cell adhesion, reduced proliferation rate and phenotypic drift [360,427]; with preclinical in vivo data showing poor cellular infiltration and mechanical properties compared to controls [428]; and with clinical evaluations showing problems with cell lysis, anchor failure, macrophage stimulation and allergic responses [429,430]. This high failure rate has been attributed to their hydrophobic nature and their lack of cell recognition signals that prevents cell attachment [391,[431][432][433][434]. To this end, scaffold-free therapies based on the principles of tissue engineering by self-assembly / cell-sheet technology are slowly, but surely, gaining more scientific and technological interest.…”
Section: Bottom-up Approached For Tendon Repair Based On Synthetic Inmentioning
confidence: 99%
“…The use of PLGA and PCL has been problematic, with in vitro data showing poor tendon cell adhesion, reduced proliferation rate and phenotypic drift [360,427]; with preclinical in vivo data showing poor cellular infiltration and mechanical properties compared to controls [428]; and with clinical evaluations showing problems with cell lysis, anchor failure, macrophage stimulation and allergic responses [429,430]. This high failure rate has been attributed to their hydrophobic nature and their lack of cell recognition signals that prevents cell attachment [391,[431][432][433][434]. To this end, scaffold-free therapies based on the principles of tissue engineering by self-assembly / cell-sheet technology are slowly, but surely, gaining more scientific and technological interest.…”
Section: Bottom-up Approached For Tendon Repair Based On Synthetic Inmentioning
confidence: 99%
“…The hand is the most common site for foreign body injuries. [1] Glass, wood, and metal are the most common materials. [2] Pencil lead injuries often occur in school-age children, frequently in the head and neck region.…”
Section: Discussionmentioning
confidence: 99%
“…[2] One study reported that 4.7% of 950 tendons retrieved at autopsy had silent foreign bodies. [1] Another study reported that 38% of retained foreign bodies in the hand were missed by the first treating physician. [2] The patient in this case also presented with no symptoms, and there was no sign of inflammation during the exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one autopsy study of patients with tendon injuries organic matter was associated with purulent tendonitis, necrosis, foreign body granuloma, fibrosis and peritendonitis and calcification. 10 Penetrating ingested foreign bodies can remain quiescent for years but can cause late mortality from diffuse and local suppurative processes especially if leading to vascular injuries. 11 …”
Section: Introductionmentioning
confidence: 99%